Methodology-driven efficient synthesis of cytotoxic (±)-piperarborenine B - Chunngai Hui; Andrey P. Antonchick (Green Synthesis and Catalysis, 2022)
The evolution of synthetic design toward the efficient synthesis of cyclobutane natural product (±)-piperarborenine B is demonstrated. Taking the advantages of good functional group compatibility of contractive synthesis of cyclobutanes from pyrrolidines, stereoselective synthesis of unsymmetric highly functionalized cyclobutanes core of (±)-piperarborenine B was realized in one step. Also, an unprecedented carboxylic acid assisted-diastereoselective Kracho decarboxylation/transmethylation features a new strategy for a non-symmetrical cyclobutane core. The synthesis of (±)-piperarborenine B illustrates the advancement of methodology resulting in the improvement in synthetic efficiency.